Prioritizing the Mental Health and Well-Being of Healthcare Workers: An Urgent Global Public Health Priority - Lene E. Søvold; John A. Naslund; Antonis A. Kousoulis; Shekhar Saxena; M. Walid Qoronfleh; Christoffel Grobler; Lars Münter (Frontiers Media S.A., 2021)
The COVID-19 pandemic has had an unprecedented impact on health systems in most countries, and in particular, on the mental health and well-being of health workers on the frontlines of pandemic response efforts. The purpose of this article is to provide an evidence-based overview of the adverse mental health impacts on healthcare workers during times of crisis and other challenging working conditions and to highlight the importance of prioritizing and protecting the mental health and well-being of the healthcare workforce, particularly in the context of the COVID-19 pandemic. First, we provide a broad overview of the elevated risk of stress, burnout, moral injury, depression, trauma, and other mental health challenges among healthcare workers. Second, we consider how public health emergencies exacerbate these concerns, as reflected in emerging research on the negative mental health impacts of the COVID-19 pandemic on healthcare workers. Further, we consider potential approaches for overcoming these threats to mental health by exploring the value of practicing self-care strategies, and implementing evidence based interventions and organizational measures to help protect and support the mental health and well-being of the healthcare workforce. Lastly, we highlight systemic changes to empower healthcare workers and protect their mental health and well-being in the long run, and propose policy recommendations to guide healthcare leaders and health systems in this endeavor. This paper acknowledges the stressors, burdens, and psychological needs of the healthcare workforce across health systems and disciplines, and calls for renewed efforts to mitigate these challenges among those working on the frontlines during public health emergencies such as the COVID-19 pandemic.